Oral Contraceptive Use and Reproductive Characteristics Affect Survival in Patients With Epithelial Ovarian Cancer: A Cohort Study. Issue 9 (November 2015) - Kolomeyevskaya, Nonna V.; Szender, J. Brian; Zirpoli, Gary; Minlikeeva, Albina; Friel, Grace; Cannioto, Rikki A.; Brightwell, Rachel M.; Grzankowski, Kassondra S.; Moysich, Kirsten B.
Abstract : Objectives: Prognostic risk factors influencing survival in patients with epithelial ovarian cancer (EOC) include tumor stage, grade, histologic subtype, debulking, and platinum status. Little is known about the impact of hormonal milieu and reproductive factors before cancer diagnosis on clinical outcome. We sought to evaluate whether oral contraceptive (OC) use carries any prognostic significance on overall survival (OS) in patients with EOC. Methods: Newly diagnosed patients with EOC, fallopian tube, and primary peritoneal cancers between 1982 and 1998 were prospectively evaluated with a comprehensive epidemiologic questionnaire. A retrospective chart review was performed to abstract clinicopathologic data, including OS. A Kaplan-Meier analysis was performed to compare survival across various exposures. A Cox regression model was used to compute adjusted hazards ratios (aHRs) and 95% confidence intervals (CIs). Results: We identified 387 newly diagnosed cancers with evaluable information in this cohort. Decreased risk of death was observed in women who reported prior use of OC (aHR, 0.79; 95% CI, 0.58–1.09), previous pregnancy (aHR, 0.77; 95% CI, 0.57–1.04), or a live birth (aHR, 0.81; 95% CI, 0.60–1.08) after adjusting for age at diagnosis, stage, and histologic subtype. Oral contraceptive use was associated with a crude reduced risk of death (HR, 0.55; 95% CI, 0.42–0.72), with reported median OS of 81 months in OC users versus 46 months in nonusers. Patients who reported a single live birth experienced the largest potential survival advantage (aHR, 0.61; 95% CI, 0.39–0.94). Oral contraceptive use and prior pregnancy were associated with improved survival across all strata. Conclusions: Oral contraceptive use may have lasting effects on epithelial ovarian tumor characteristics conferring favorable prognosis. Putative mechanisms that affect tumor biology include complex interactions between ovarian cells, host immune cells, and hormonal microenvironment during carcinogenesis. Future efforts should be directed to determine the role of reproductive factors in antitumor immunity.